Clinical Application of Stem Cell Therapy for Liver Cirrhosis: Progress, Pitfalls, and Prospects - Prenali Dwisthi Sattwika; Fahmi Indrarti; Putut Bayupurnama (Acta Medica Indonesiana, 2022)
Liver cirrhosis is the advanced stage of liver disease accounting for high morbidity and mortality rates worldwide. Liver transplantation for liver cirrhosis has several limitations, rendering stem cell transplantation as a potential therapy. Clinical trials of stem cell applications for liver cirrhosis are being established using various types of stem cells. This review will provide a current report of the achievements, limitations, and future directions of stem cell transplantation. Current progress of clinical trials is valuable in defining the best type of stem cells, mode of delivery, the number and frequency of cells to be injected, and determining potential candidates for cell therapy. Some of the encountered pitfalls are the limited homing and differentiation potential of stem cells, the use of non-xenofree culture system, and the risk for tumorigenesis in certain types of stem cells. The prospective developments of liver stem cell transplantation are the generation of genetically modified stem cells and the formation of liver organoids for treating liver cirrhosis.